Dançando o phásma: a performance do conflito sírio na dança-teatro contemporânea - Raposo, Sílvia (2022)
This article proposes an analysis of theatrical dance from the performance/politics binomial in which the body is seen as a privileged place to the analysis of power, since a body when dancing always takes a stand on political field. To do this, we try to contextualize the dance-theatre of the shows "Antes que Matem os elefantes", by Companhia Olga Roriz and "Eu Sou Mediterrâneo", by Companhia Vidas de A a Z, in their artistic course and analyse their coreographical and scenic languages having in view an understanding of the body that dances as a body that undergoes the actions of power relations, analysing it as a place of tension and clashes that develops articulations with memory and forgetfulness in a sensory-corporal game, speaking of the body as an archive and as a place of memory and resistance and look at it as a privileged place for the analysis of power.